7t-9=3(y+5)

Simple and best practice solution for 7t-9=3(y+5) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7t-9=3(y+5) equation:


Simplifying
7t + -9 = 3(y + 5)

Reorder the terms:
-9 + 7t = 3(y + 5)

Reorder the terms:
-9 + 7t = 3(5 + y)
-9 + 7t = (5 * 3 + y * 3)
-9 + 7t = (15 + 3y)

Solving
-9 + 7t = 15 + 3y

Solving for variable 't'.

Move all terms containing t to the left, all other terms to the right.

Add '9' to each side of the equation.
-9 + 9 + 7t = 15 + 9 + 3y

Combine like terms: -9 + 9 = 0
0 + 7t = 15 + 9 + 3y
7t = 15 + 9 + 3y

Combine like terms: 15 + 9 = 24
7t = 24 + 3y

Divide each side by '7'.
t = 3.428571429 + 0.4285714286y

Simplifying
t = 3.428571429 + 0.4285714286y

See similar equations:

| (7u-5)^1/2=(9u-15)^1/2 | | 3x+63=84 | | y=-px+q | | 0.09Xx=144.39 | | 19=x-y | | 5(t-2)=1+10 | | 30=5(x+10) | | x+b+c(m)=x | | 3400=x^2+60x+1800 | | 1x=x | | 3x^2-5x-99=0 | | -5/2(5/7) | | y=3/2(x-8) | | 1/3x-6=2 | | 11.4-22.5z=84.1 | | 18-2x=3x-7 | | -12=-3w+-3 | | 5/x-8=6 | | 7(3x-11)-2(-2x-5)+9= | | y=695.6+-0.6c | | 9x/10b*2xb/3x^2 | | 1-4d=-19 | | 1-14=-19 | | 45=.75x | | 5.2x+1=4.2x | | 4x^2=x^2+2 | | -4x+10=-2x-6 | | A*6+8=38 | | 9x-3y-9=0 | | 40x+30x=55 | | X^2+4x+10=-3 | | 8x^2=-40+48x |

Equations solver categories